The Interaction between Spaced Learning breaks and Cognitive Style to enhance Mathematical Problem-Solving Skills for High School Students - Mohamed Tawfik, Mahmoud Fahmy (Technium: Romanian Journal of Applied Sciences and Technology, 2025)
This research aimed to measure the impact of the interaction between the patterns of spaced learning breaks (physical-electronic) and the cognitive style (ambiguity tolerance-ambiguity intolerance) on enhancing mathematics problem-solving skills for high school students in the State of Qatar. The research sample consisted of 60 male and female 12th-grade students from Qatar High School in Al-Kheesa. They were divided into four experimental groups based on their cognitive style and the pattern of spaced learning breaks provided to them, following the quasi-experimental research design. The measurement tools included the Cognitive Style Test (ambiguity tolerance – ambiguity intolerance) and the Mathematics Problem-Solving Skills Test. The results revealed a statistically significant positive interaction effect at the 0.05 level between the spaced learning break pattern (electronic vs. physical) and the cognitive style (ambiguity tolerance vs. ambiguity intolerance) for students in the four groups in the post-test of mathematics problem-solving skills. Additionally, the findings showed statistically significant differences at the 0.05 level in favor of the group that learned through the electronic spaced learning break pattern, as well as in favor of the students with ambiguity tolerance, in terms of their problem-solving skills in mathematics.